2007
DOI: 10.1002/nur.20181
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the eyberg child behavior inventory with African–American and Latino parents of young children

Abstract: This study evaluated the reliability, equivalence, and convergent validity of the Eyberg Child Behavior Inventory (ECBI) in 682, 2- to 4-year-old children. For analysis, parent informants' data were blocked by race/ethnicity (African-American, Latino, non-Latino White), family income (low versus middle/upper), child's gender, and ECBI language version (English and Spanish). ECBI scales had high internal consistency reliabilities and good convergence with the Child Behavior Checklist/1-5. Some racial/ethnic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…Findings from this study indicate that a unidimensional structure of the ECBI Intensity Scale is appropriate for young African American and NLW children from low income backgrounds. These findings, in addition to previous findings of single-factor measurement equivalence across racial groups (Gross et al, 2007) suggest that total ECBI Intensity Scale scores can confidently be used to screen and evaluate treatment outcomes in diverse racial/ ethnic samples that include young low-income African American and NLW children. However, our inability to demonstrate discriminant validity of the ECBI Intensity Scale with the CBCL Anxious/Depressed subscale was unexpected.…”
Section: Discussionmentioning
confidence: 55%
“…Findings from this study indicate that a unidimensional structure of the ECBI Intensity Scale is appropriate for young African American and NLW children from low income backgrounds. These findings, in addition to previous findings of single-factor measurement equivalence across racial groups (Gross et al, 2007) suggest that total ECBI Intensity Scale scores can confidently be used to screen and evaluate treatment outcomes in diverse racial/ ethnic samples that include young low-income African American and NLW children. However, our inability to demonstrate discriminant validity of the ECBI Intensity Scale with the CBCL Anxious/Depressed subscale was unexpected.…”
Section: Discussionmentioning
confidence: 55%
“…Among representative samples, the ECBI has been shown to have good properties of test-retest reliability (a ¼ .86-.88), internal consistency (a ¼ .88-.95), and concurrent validity with other validated measures (Boggs, Eyberg, & Reynolds, 1990;Rich & Eyberg, 2001). The ECBI also has demonstrated sound reliability and validity with African American and Latino samples (Gross et al, 2007).…”
Section: Instrumentsmentioning
confidence: 96%
“…Although prior research has found differences in challenging behavior between Caucasian children and children of minority backgrounds (Konold et al, 2003), there were no significant differences between children of different racial/ethnic backgrounds on the ECBS challenging behavior subscale. However, the sample of the current study was predominately low-income, and it has been noted that past research on racial/ethnic differences in prevalence rates of behavior problems traditionally has been confounded by socioeconomic differences (Gross et al, 2007). Low SES is consistently identified as a factor that places children at an increased risk for the development of behavior problems (Chapman, Dube, & Anda, 2007;Rutter, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have investigated the psychometric properties of the ECBI (Eyberg & Pincus, 1999;Gross et al, 2007). The ECBI has excellent internal consistency (.93-.95; Burns & Patterson, 1990).…”
Section: Methodsmentioning
confidence: 98%